2002
DOI: 10.1177/070674370204700321
|View full text |Cite
|
Sign up to set email alerts
|

Acute Onset of Schizophrenia following Autocastration

Abstract: ex clud ing in di vidu als ex press ing no opin ion rep re sent equally invalid methods of in flat ing the ap par ent ac cep tance of dis so cia tive dis or ders and do not make a large nu meri cal dif fer ence, in any case.Sim ply stated, one may choose to in terpret our find ings as show ing that the glass is ei ther half-full or half-empty (as we have noted be fore [3]), but by any standard one can not claim that there is any con sen sus one way or the other on the diag nos tic status or sci en tific va lid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Reports of MSM in association with substance abuse and affective psychosis are rare, but the characteristics of these patients are similar to those with a schizophrenia spectrum psychosis. Temporality: We only found 2 cases in which MSM may have preceded over psychosis, 28,62 although it is also possible that some of the cases in which psychosis was not diagnosed were in the prodromal phase of psychotic illness. Biological gradient: The cases examined in this study had severe psychotic illness with numerous acute symptoms.…”
Section: Psychosis and Causation Of Msmmentioning
confidence: 90%
“…Reports of MSM in association with substance abuse and affective psychosis are rare, but the characteristics of these patients are similar to those with a schizophrenia spectrum psychosis. Temporality: We only found 2 cases in which MSM may have preceded over psychosis, 28,62 although it is also possible that some of the cases in which psychosis was not diagnosed were in the prodromal phase of psychotic illness. Biological gradient: The cases examined in this study had severe psychotic illness with numerous acute symptoms.…”
Section: Psychosis and Causation Of Msmmentioning
confidence: 90%
“…Kulkarni et al (2012) recently reviewed this hypothesis and suggested that estrogen may offer a novel therapeutic strategy. Alternatively, the testosterone-protection hypothesis states that testosterone protects against schizophrenia by modulating the neurotransmitters implicated in the disorder (Duggal et al, 2002). Testosterone also plays a neuroprotective role in the brain (Hammond et al, 2001), and lower testosterone in patients with schizophrenia was associated with a greater number of negative symptoms (Akhondzadeh et al, 2006).…”
Section: Potential Etiopathological Mechanisms For Gm Abnormalities Amentioning
confidence: 99%
“…Duggal et al . [ 96 ] and Shriharsh et al . [ 97 ] face problems implementing proper cognitive-behavioral techniques in schizophrenia patients.…”
Section: Resultsmentioning
confidence: 99%
“…Errors happened in the areas of the therapist’s understanding of the basic premise of therapy, theoretical underpinnings of the therapy, gross neglect of therapy structure, use of non-specific terminologies and poor descriptions, over-inclusiveness, use of outdated techniques like JPMR. [ 23 24 25 26 27 28 48 49 51 52 53 54 77 78 79 80 81 82 84 85 86 87 88 89 90 91 92 95 96 97 98 99 100 ]…”
Section: Discussionmentioning
confidence: 99%